Climate-Smart Agriculture (CSA) within the Feed the Future Project Portfolio of USAID-Zambia: A CCAFS Deep Dive Review - White, Douglas; Bonilla Findji, Osana; Schreeg, Laura; Jarvis, Andy (2016)
As part of a global effort that will inform how Feed the Future tracks CSA across the 19 focus countries (plus aligned) the CCAFS and USAID/BFS team selected 5 to carry out a deeper analysis of their portfolio. A visit in May 2015 by staff from CCAFS and USAID-BFS Washington to the Zambia Mission provided an opportunity to identify and discuss CSA-related activities within the country and the USAID zone of influence (ZOI). The five-day visit included a series of meetings with Mission staff, implementing partners of Feed the Future projects, agency personnel of the Government of Zambia, and the FAO-Zambia CSA specialist. The discussions were preceded by a document review of projects in the Feed the Future portfolio, shared in advance of the visit by the Mission, and other agriculture and climate change information available on the web. This report outlines key findings of the visit and suggests ways in which CSA can be further integrated into upcoming Feed the Future programming in Zambia. Although climate change has been a key theme in FtF, considerations are under way for CSA being an explicit cross-cutting theme. Five countries were selected for visits. Results from these inquiries will inform how FtF tracks CSA across the 19 focus countries, plus aligned countries.